Analisis Penggunaan Aplikasi Canva dalam Peningkatan Kemampuan Desain Grafis Mahasiswa - Farman, Indra; L, Muhammad Hidayat; Ade Marela; Yusniati (Program Studi Pendidikan Teknologi Informasi Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2024)
Education is one of the main pillars in producing a generation that is competent and ready to face various challenges in the future. In the era of globalization and industrial revolution 4.0, education is one of the main pillars in forming a generation that is competent and ready to face various challenges in the future. In the era of globalization and industrial revolution 4.0, this research aims to determine the increase in student creativity by using the Canva application. The research method used is descriptive qualitative. The research subjects are students of the Information Technology Education Study Program Class of 2023. Data collection techniques were carried out using interviews, observation and documentation. The results of the research carried out increase their efficiency and productivity in completing graphic design tasks. Compare with other editor applications